Neuroprotective effects of erythropoietin during deep hypothermic circulatory arrest☆ - Givehchian, Mehdi; Beschorner, Rudi; Ehmann, Cornelius; Frauenlob, Lydia Michaela; Morgalla, Matthias; Hashemi-Kalibar, Seyed-Bahram; Ziemer, Gerhard; Scheule, Albertus Maria (European journal of cardio-thoracic surgery, 2010)
Objective: Permanent mild-to-severe brain injury with neurologic sequelae remains a significant source of postoperative morbidity in cardiovascular surgery. There is increasing evidence that erythropoietin confers neuroprotective effects in various conditions of neuronal damage, such as hypoxia and cerebral ischaemia. Using a surviving porcine model, this study evaluates whether systemic treatment with erythropoietin induces brain protection in deep hypothermic circulatory arrest (DHCA). Methods: Sixteen pigs (42 ± 3 kg) randomly assigned into two groups (n = 8) were subjected to 60 min of DHCA at an intracerebral temperature of 20 °C. The animals of the erythropietin group were treated perioperatively with 500 IU kg−1 of recombinant human erythropoietin on 3 consecutive days beginning the day before surgery. Intracerebral monitoring was performed by subcortical microdialysis, brain tissue oxygenation, measurement of brain temperature and intracranial pressure. Neurologic recovery was evaluated daily. Perioperative S100β protein serum level was determined. The brains were harvested on the postoperative day 6 after perfusion fixation. Multiple brain regions were investigated histologically for hypoxic-ischaemic damage. Results: The subcortical brain microdialysis detected significant increase of glycerol and lactate concentrations in both groups (P = 0.0001) with considerably higher concentrations in the brain of control animals (P = 0.011). There were no significant differences in neurological outcome (P = 0.15). Erythropoietin-treated animals tended to a more complete and rapid neurological recovery. By contrast, none of the animals in the control group achieved complete neurological recovery. S100β protein as a putative marker of cerebral injury tended to be higher in the control group. Brain infarction was detectable in all control animals but only in two erythropoietin-treated animals. Conclusion: These results suggest some beneficial neuroprotective effects of erythropoietin in this model of global brain ischaemia induced by 1 h of hypothermic circulatory arrest.
Available online 19 September 2009
Gesehen am 28.03.2023